Investigating the Cultural and Social Effects of Football among the Students of Physical Education Department at Kandahar University - Enayatullah Dadman; Sultan Mohammad Stanikzai; Khalid Amarkhil (Indonesian Journal of Sport Management, 2023)
The aim of this study is to investigate the socio and cultural effects of football among the Students of the Physical Education Department at Kandahar University The foot obviously has a lot of symbolic significance. Because football is primarily played with the foot, it has issues with identity, class, and history. Due to its connection to the "common man" and the masses, its appeal, and its role in fostering liberation, football has risen to the top of the cultural consciousness, transcending sport and turning into a religion. This is a result of these issues. Nations attach their identities to football matches, making them symbols of so much more than just a game or a rivalry. Football is a venue for social and political discussion. Thus, it turns into a lens through which we can understand various social systems all over the world. Sport is both. This study used a descriptive qualitative methodology. The findings of this study show that the game of football has many advantages for football players, one of which is improved physical health. Football players engage in rigorous training to help them develop the strength, stamina, and other crucial qualities needed for football games.